People's Republic of China Financial Sector Assessment Program : Insurance Core Principles - International Monetary Fund; World Bank (Washington, DC, 2017)
The Chinese insurance sector is experiencing rapid growth, posing particular challenges to effective supervision. The sector has been growing by over 20 percent a year and there are ambitious government targets for further development. Many individual, often newer, companies are growing at rates far in excess of the average. New entrants, products and distribution channels, combined with the liberalization of pricing, have increased competition. At the same time, slower economic growth and reduced investment returns are exposing many established life insurers to the risk of loss due to the rising value of their liabilities. Many non-life companies are moving into new lines of business as margins in established lines erode. While their customers continue to benefit from a dynamic market, there are risks to insurance companies’ business models, performance and to solvency as well as risks of misconduct in the treatment of insurance customers. There are particular challenges for insurance supervisors to remain abreast of developing risks, while continuing to strengthen the regulatory and supervisory system for the longer term. The China Insurance Regulatory Commission (CIRC) has been undertaking far-reaching reforms and modernization since the 2011 FSAP. It has focused its work on improving corporate governance, enforcing sound market conduct and reshaping the solvency standards into a modern, risk-based approach. The China-Risk Oriented Solvency Standards (C-ROSS) draw on international practices and experience in the Chinese market to define solvency requirements that generally reflect risk as well as rewarding sound risk management. By linking the framework to an in-depth assessment of risk management, C-ROSS has also equipped CIRC with a strengthened overall supervisory framework for solvency risk. As a result, CIRC has felt confident to relax or remove less risk-based requirements such as new product (and reinsurance contract) approval as well as detailed limits on insurers’ investments. In parallel with regulatory changes, it has been working to reform and develop the insurance market, liberalizing pricing controls and accommodating the development of new products, although restrictions remain on the access of foreign insurers, especially in life insurance.